The role of Islamic political parties in the contemporary political affairs: Case study of Al-Nahdah political party in Tunisia / Bara Barakat Hamad Algharibeh - Bara Barakat , Hamad Algharibeh (2016)
The topic of Islamic parties and their role in contemporary political life occupies a special and important place and ranks highly among the topics frequently discussed and debated in the contemporary political arena since the herald of the end of the Western occupation of the Arab world in the middle of the twentieth century. And recently, the events that took place early in the second decade of this century, termed as ‘The Arab Spring’, significantly added more importance to the role of these parties and gave more prominence to the Islamic movements which are known as “the stream of political Islam". In order to describe and analyze a political system in any country, the various forces that are involved in the exercise of power and influence, whether directly or indirectly, need to be clearly identified. The authorities and institutions related to decision-making processes within any political system, are not only the ones comprising the executive, legislative, judicial and administrative structures, but those also encompass the political groups and blocs of parties and organizations. This study sought to explain the concept of ‘party’ linguistically, conventionally and from the Islamic legislative point of view, and it established the meaning of the “Islamic Party” concept. It explored the emergence of the ‘party’ concept in the Islamic political system; it attempted to clarify the foundations of the Islamic Party, its targeted goals, and the approach it follows; and it demonstrated the Islamic legislation points of view related to political pluralism. The Tunisian “Annahdha (Renaissance) Movement” party was adopted as a model for this study. The party’s emergence, its development, the political situation at the time, and the nature of the relationship between religion and state have been researched. This study also attempted to analyze the Islamic phenomenon in Tunisia, and to identify the reasons and motives driving the Tunisian revolution at the end of 2010. The study vi also discussed the role of parties, especially the Islamic ones. It started researching the relationship between the parties and society. It has come up with answers to the question regarding the role that was established and practiced by political parties with Islamic reference in general, and the role of the “Annahdha (Renaissance) movement”, in particular. It also highlighted the challenges that faced the Islamic parties, and identified the practices and responses of “Annahdha movement” toward these challenges, and its adherence to its proclaimed adopted political approach to the issues of the state and democracy, and to clarify the party's viewpoint with respect to them. The choice of the research topic ‘The role of Islamic parties in contemporary political life: Annahdha Movement in Tunisia” party as a model, was motivated by the hope of contributing to the efforts of discussing one of the most lively and sensibly debated topics of our modern time, as it distinctly involves a broad partnership in the fields of legislation and politics. It was also motivated by the desire of providing a scientifically researched material bearing different visions, discretions and interpretations, in the hope of adding a new contribution to studies of Islamic political theory.